An Examination of the Relationships between Integrated Leadership, Organizational Structure and Public Sector Performance in Egypt - Hassanein, Abdelrahman (AUC Knowledge Fountain, 2021)
This thesis investigates how integrated leadership mediated by organizational structure, affects organizational performance in three Egyptian public sector institutions. The aim of this research is to identify the key challenges in these three areas (leadership, organizational structure and performance) and provide recommendations for improvement. The study adopts a mixed method approach, including both quantitative and qualitative analysis. The qualitative element consisted of in-depth interviews of organizational leaders and participant observation. Employee surveys and interviews with leaders were conducted in three public organizations located in Greater Cairo. Two of these organizations are project implementations units (PIUs), whilst one is a traditional public sector bureaucracy. The findings of both the quantitative and qualitative analyses suggest that integrated leadership, mediated by a supportive organizational structure, positively enhances employee performance in the Egyptian public sector. To overcome the enduring problem of low performance in the public sector, this study recommends that policy makers focus on adopting elements of integrated leadership and enhancing a supportive non-bureaucratic public organization in the various public institutions, PIUs and parallel started structures.